Ontology-Based Source Code Retrieval Model To Support Program Comprehension - Kadar, Rozita (2019)
Identifying the parts of source code corresponding to a specific functionality is one of the most common activities undertaken by software maintainers while performing maintenance tasks. This task is a key challenge to them since they need to comprehend a software system in advance. Various techniques have been proposed to help software maintainers to reduce their effort in finding location of source code concern. Concept location is one of the techniques that able to provide a solution to the problem. The most common technique to support concept location is text retrieval. Therefore, this study focuses on the use of source code for text retrieval technique in identifying relevant location to be maintained. The contents of data source that use as an information in source code retrieval process is one of elements that able to improve the performance of the technique.